Stereochemistry and ab initio topology analyses of electron lone pair triplets and twins in interhalogen compounds and halogen suboxides. (December 2017) - Matar, Samir F.; Couegnat, Guillaume; Galy, Jean
Abstract: The paper reports a thorough investigation of little inspected two classes of group VIIA based crystals: interhalogen compounds ClF, ClF3, BrF3 and IF3 on one hand and halogen suboxides F2 O, Cl2 O and Br2 O on the other hand, as well as rare gas fluorides (here exemplarily XeF4 ), all exhibiting peculiar stereochemistry of electron (non-bonding) lone pairs merging in forms of twins and triplets. Particularly with respect to the well known VSEPR (Valence Shell Electron Pair Repulsion) model we present original approach merging crystal chemistry and density functional theory (DFT) electron localization function (ELF) to provide accurate topologic analyses and precise metrics of electron lone pairs geometries. In this context we rewrite the chemical formulae above by adjoining E designing the lone pair (LP) and M* formulating the LP-bearing element: ClFE3 , M*2 OE2 {E3 }2 (M* = F, Cl, Br), M*F3 E2 (M* = Cl, Br, I) and XeF4 E2 . Then in ClFE3 and M*2 OE2 {E3 }2 (M* = F, Cl, Br) family an original stereochemistry is developed with LP concentration in E triplets which generate electronic torus revolving around Cl and M* which in the neighborhood of largely electronegative F, exhibit cationic-like behavior. E around Cl in ClF and then around M* of the series under consideration exhibits an ellipsoidic shape with an equivalent sphere of influence radius (rE ) increasing along with the atomic number Z, i.e. rE_F = 0.52 Å, rE_Cl = 0.65 Å and rE_Br = 0.70 Å. From selected sections in ELF data we obtained precise topology and metrics details of these tori. For M*2 OE2 {E3 }2 family the E twins attached to O have also been localized, their size remaining constant with rE_O = 0.68 Å in all studied compounds. The lone pair twins in the series M*F3 E2 (M* = Cl, Br, I; M* trivalent oxidation state) as well as in noble gas tetrafluoride XeF4 E2 provide remarkable examples: rE evolution versus Z, rE_Cl = 0.77 Å (Z = 17), rE_Br = 0.85 Å (Z = Br) and rE_I = 0.90 Å (Z = 53), follow a linear expansion while in the xenon case with a close ZXe = 54 but with tetravalent oxidation state, Xe exhibits a radius rE_Xe = 0.95 Å, indicating the important influence of the charge magnitude on E volume. The interaction of cations with E centroïd: Ec -defined as the electronic volume attached to the lone pair- of neighboring molecules is plausible in explaining unusually short distances between cations. Even surrounded by E torus the cations obviously exert attractive influence through its vortex axis. Based on combined stereochemistry and ab initio topology analyses the paper endeavors showing the unavoidable necessity to accurately account for electron lone pairs: – position of their centroïd, – their shape, – their size, – and their deformation (knowing that the electron cloud which accompanies them exhibits a certain plasticity), in order to fully understand their remarkable influence on crystal networks.